A two-directional approach to pyrrolizidines: total syntheses and biological evaluation of alkaloid cis-223B and (+/-)-xenovenine - Barthelme, Alexandre; Richards, David; Mellor, Ian R.; Stockman, Robert A. (Royal Society of Chemistry, 2013)
Total syntheses of alkaloid cis-223B and xenovenine are reported in 3 and 4 steps respectively using a two-directional synthesis/triple reductive amination strategy, and their neurotoxic properties assessed.